ANALISIS PENGARUH PROMOSI, KUALITAS PRODUK DAN LAYANAN PURNA JUAL TERHADAP MINAT BELI SEPEDA MOTOR YAMAHA ( Studi Kasus Mahasiswa Ekonomika Dan Bisnis Universitas Diponegoro Semarang ) - Aryatama, Nicko Bintang; Kamal, Mustofa (Faculty of Economics and Business Diponegoro University, 2015)
This research purposed to find out the influence of promotion, the quality of product and after sales against interest buy yamaha motorcycle and analyzing the most dominant factor in influencing consumer interest in purchasing yamaha motorcycle used student of diponegoro university in semarang.This research used samples totaled 100 people taken from consumers who buy and use yamaha in the faculty of economics and business Diponegoro University of semarang obtained by used technique purposive sampling. Then kinds of analysese against the data obtained quantitative analysis. Quantitative analysis covering test validity test reliabilitas, test classic assumtions, test multikolinearitas, test heterokedastisitas, test normality, multiple regression analysis, F test , t test, a coefficient of determination. The data have met, test the validity of reliabilitas, and the assumption of the classical tillable so as to produce the regression equation is as follows:Y = 0,264 X1 + 0,320 X2 + 0,333 X3Individually order from each of the most influential variable service after sales with the regression coefficient of 0,333 and variable the quality of the product with the regression coefficient of 0,320. While variables its influence the lowest is promotion with the regression coefficient of 0,264. The model equation having value fastene count rp59.22 47.436 and extent of signification 0,000 and extent of signification smaller than ( 0.05 ). It shows that the independent variable promotion, quality of the product and aafter sales has influence significantly to interest in buying.